An Investigation of the Modified Nerve Impulse Saltatore Conduction Model - V. V. Mayorov; S. E. Anufrienko (Моделирование и анализ информационных систем)
In the article it is considered the Nerve Impulse Saltatore Conduction model in which the Impulse Neuron model modification is used for describing Ranvier Interruptions dynamics. The model contains ordinary differential equations and delay differential equations. The system is investigated by the asymptotic step-by-step integration method. All results were obtained analytically.